Pharmacology and Clinical Efficacy of Semaglutide in the Management of Type 2 Diabetes Mellitus: Review Article (Journal of Pharma Insights and Research, 2025)
Semaglutide, a long-acting glucagon-like peptide-1 (GLP-1) receptor agonist, represents a significant development in the therapeutic landscape for type 2 diabetes mellitus (T2DM). Its molecular structure, featuring 94% homology to human GLP-1 with modifications for albumin binding and resistance to dipeptidyl peptidase-4 (DPP-4) degradation, confers an extended half-life of approximately one week. This profile permits once-weekly subcutaneous or, uniquely, once-daily oral administration facilitated by the absorption enhancer sodium N-(8-[2-hydroxybenzoyl]-amino) caprylate (SNAC). The mechanism of action involves glucose-dependent stimulation of insulin secretion, suppression of inappropriate glucagon release, and delayed gastric emptying. Apart from glycemic control, semaglutide exerts central effects on appetite regulation, leading to significant reductions in body weight. Large-scale clinical trial programs (SUSTAIN for subcutaneous, PIONEER for oral) have shown robust reductions in HbA1c and body weight compared to placebo and active comparators, including other GLP-1 receptor agonists and SGLT2 inhibitors. Moreover, dedicated cardiovascular outcome trials have established its benefit in reducing major adverse cardiovascular events (MACE) in patients with T2DM and high cardiovascular risk. Its clinical utility extends to chronic weight management, with higher-dose formulations approved for obesity. The primary adverse events are gastrointestinal in nature, including nausea, vomiting, and diarrhea, which are typically dose-dependent and transient. Therapeutic monitoring include potential risks for diabetic retinopathy complications and the class-specific boxed warning regarding thyroid C-cell tumors, derived from rodent studies